Analysis of Personal Spt Report 1770,1770s, 1770ss, in Fiscus Compliance with Payment Tax on Income of Employee in Indonesia Telecommunication Industry (Pt. Pt.Inti Persero)2017 2018 - Supardi,; Asikin, Bachtiar (International Journal of Psychosocial Rehabilitation, 2020)
Reducing dependence on external financial resources, especially overseas programs, the Indonesian government is continuously trying to improve the state of financing sources and the development of the country as well as internal development, i.e., internal sources of development financing come from government oil and non-oil and gas that is the recipient of tax and non-tax. The study was conducted at PT. Indonesian Telecommunications Industry (Persero) (PT. INTI), which is engaged in the telecommunications industry, the company whose shares and capital are 100% owned by the government. This research was conducted to obtain empirical evidence regarding establishing tax compliance in paying taxes. The research design used in this study was a survey (survey design). Researchers conducted two stages, namely the first stage to test compliance with the submission of tax returns and taxpayers in fulfilling their tax obligations, and the second stage was testing of irregularities. The conclusion shows that there is a link between the level of compliance before and after the inspection checks. Based on the results of research on the influence of individual characteristics of the taxpayer, the characteristics of the company, and ownership structure on the level of tax compliance, which is carried out at 102 taxpayers. There are five factors that make up the individual characteristics of the taxpayer, including educational qualifications, family relationships, understanding of the taxpayer, the use of information technology, and communication